Complexity and dissipation, chaos and information in the technological novel - Muirhead, Marion Eleanor (University of Waterloo, 1999)
In White Noise by Don DeLillo, Gravity's Rainbow by Thomas Pynchon, Neuromancer by William Gibson, and Already Dead: A California Gothic by Denis Johnson, scientific paradigms influence the conceptualization of time, of space, and of information. The feedback loop in complex systems dynamics represents the reiteration of processes over time, with each repetition describing a self-similar but non-identical pattern. This conceptualization of the feedback loop differs from that of cybernetics, in which the loop is identically reiterated on each repetition. The point at which one repetition ends and another begins constitutes a bifurcation point which, in some cases, takes the form of a singularity. In the novels under consideration, these patterns appear within the narrative structure as well as in descriptions of space, time, and behaviour, particularly in the patterns of consumption of the characters and in the proliferation of information- and misinformation - in the mass media. Repetitions within the narratives undermine the effects of linear plotting. Space appears as layered interiority and exteriority with an equivocal point, often a singularity, in the liminal region. In Pynchon's schema, time slows to infinity at the singularity and, at this singular point, the image attains a power and significance that transcends human cognition. Within the chaotic paradigm, the novel can be described as a dissipative structure in which a state of maximum entropy precedes a leap to a new level of organization. The four novels under consideration represent social entropy in technological society, with the human subject defined in relation to the machine and to informational systems in which the human being constitutes a compilation of statistics or data. Social entropy has been defined as the encroachment of the machinic upon the organic, or as a convergence between or a suturation of the organic and the machinic in machine culture. Symptoms of social entropy include a proliferation of mass-produced consumer goods and a corresponding proliferation of human beings who resemble each other without any sense of uniqueness or individuality, who are conditioned by the mass media to belong to target market groups for the consumption of goods and information, or, more aptly, of misinformation.
Keywords: Harvested from Collections Canada